Pais que retornam a residir com os filhos na velhice: novas ou velhas parcerias? - Santos, Valeria Lima Antunes dos (2005)
The increase in longevity in Brazil has repercussions on all the social layers; there has been a growing concern about aging. Medical sciences and technology have been offering a better quality of life to the aging being. However, how can one live these extra years with dignity, having their rights guaranteed? In our society, the family still is the link between the individual and the community in which this subject is inserted. Therefore, it is the main spring that launches the subject to life. Consequently, it is responsible for the being that is formed. It is necessary to think about the cares that are the responsibility of that institution towards its older members, when these affective bonds remain strong. The present work aimed to investigate how the elderly person perceives the family institution nowadays, how he relates to the different generations, what difficulties he encounters in this relationship, and how he organizes himself internally before the contradictions. To achieve this, the qualitative analysis allowed to understand, through the look of this old subject, how he faces this new transition period and the way in which he continues the life projects that had been postponed. It was possible to identify an increasing commitment of this age segment to taking into their own hands the success for achieving what they consider significant. Although living with the family, the elderly person demonstrates that he preserves the autonomy and responsibility for his choices.